Structural Equation Modelling (SEM) Method In The Analysis of Affecting Factors Student Achievement With The System Learning Online - Mhd Fariyanda (JMEA : Journal of Mathematics Education and Application, 2023)
Online college learning systems must be performed effectively in order for students to achieve. There are some factors that influence a student's feat of learning whether it is a factor within a student or factor outside of a student. The study was done with a view to discovering any construction that affected the performance of student learning. The method used was the Structural equation Modelling (SEM). Research materials are the results of the 2017, 2018 and 2019 advanced student studies of students from the university of Sumatra, using a simple random sampling technique. Data analysis obtained parameters: coefficient lecturer.044, coefficient 063 student and coefficient campus 0.190.